Retrograde approach for chronic total occlusion percutaneous revascularization. (June 2010) - Galassi, Alfredo R; Tomasello, Salvatore D; Costanzo, Luca; Tamburino, Corrado
Coronary chronic total occlusion represents the most challenging lesion subset for interventional cardiology. Among other new techniques and developments, the retrograde approach via collateral channels in coronary angioplasty for chronic total occlusion can improve recanalization success rates. Most interventionalists will meet few cases where the retrograde approach might provide unequaled advantages, yet many are held back from choosing the retrograde approach owing to a lack of proper equipment and expertise. This article provides a detailed description of all techniques used to traverse the collateral channels and to cross the chronic total occlusion by the retrograde approach. It also illustrates the difficulties in collateral channel crossing using different examples to provide a basic guide for case selection purposes.